2008
DOI: 10.1016/j.agrformet.2008.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Parameterisation of aerodynamic roughness over boreal, cool- and warm-temperate forests

Abstract: 1Roughness length and zero-plane displacement over boreal, cool-and warm-temperate 2 forests were observed and parameterised using forest structure data. Previous mod-3 els for roughness length and zero-plane displacement using leaf area index and 4 frontal area index did not describe intersite differences, and the model for zero-5 plane displacement did not express seasonal variations with the change of leaf area 6 that was smaller in dense forest than in sparse forest. The observed results show 7 that inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 28 publications
0
85
0
1
Order By: Relevance
“…Additional studies [43,44,47] have indicated that vegetation vertical parameters (i.e., the height and FAI) are critical for estimates of d and z 0m obtained via remote sensing-based roughness models [42][43][44]. However, few studies have focused on the long term parameterization scheme of d and z 0m while considering the variation of vertical vegetation information over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional studies [43,44,47] have indicated that vegetation vertical parameters (i.e., the height and FAI) are critical for estimates of d and z 0m obtained via remote sensing-based roughness models [42][43][44]. However, few studies have focused on the long term parameterization scheme of d and z 0m while considering the variation of vertical vegetation information over time.…”
Section: Discussionmentioning
confidence: 99%
“…Here, dynamic forest vertical information for height and the FAI were obtained from field calibrated regression models and interannual forest AGB variations in order to drive the SD model. Instead of the arithmetical mean height, the Lorey's height was derived due to the fact that it is a better expression for forest stand status, as well as for d and z 0m [44,47]. Although the R 2 values (0.52 and 0.36) of both fittings were not high, the RMSEs (2.35 m and 0.35 were relatively low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the relationship between z om and the LAI needs further study. For forests, z om /h is a function not only of the LAI, but also of a density parameter, such as the frontal area index (Schaudt and Dickinson 2000) or stand density (Nakai et al 2008a). However, data on the frontal area index and stand density were not easy to obtain thus far.…”
Section: Final Determination Of D and Z Ommentioning
confidence: 99%
“…Van Dijk et al (2004) found that z om /h is 0.03 for a rain-fed cropping system with maize and cassava rotations. Some researchers have parameterized z om as a function of h, frontal area index or leaf area index (LAI) (Schaudt and Dickinson 2000;Nakai et al 2008a). However, empirical estimates of z om are still used in many models.…”
Section: Introductionmentioning
confidence: 99%